Analisis Keberlanjutan Budidaya Jeruk Malang Melalui Pendekatan MDS (Multidimensional Scaling) - Anita Qurania; Siti Asmaniyah Mardiani (Universitas Islam Malang, 2023)
This research is the first step to find a model for cultivating citrus plants with high yields but not damaging the environment. The habit of citrus farmers to use chemical fertilizers excessively can increase the risk of environmental damage which causes citrus cultivation activities to become unsustainable. This condition requires efforts to minimize the impact, namely by designing a cultivation practice model so that citrus production centers are guaranteed to be sustainable. Sustainability analysis related to cultivation practices applied by farmers is an important indicator to determine the sustainability of citrus production centers in Malang. A multidisciplinary approach is used to evaluate the sustainability of Plantation activities. The study of the sustainability of citrus production in Malang in order to obtain information about the things that underlie environmental and production functions in citrus cultivation has not been carried out in an integrative manner, so the aim of this research is to determine the status of sustainability of citrus cultivation in Malang. Sustainability analysis can be used as a basis for compiling recommendations for the development of orange production centers that are effective and in accordance with the green economy program so that a sustainable citrus cultivation model is obtained. The analytical method used in this study is the Rap method (Rapid apprisal) with the MDS (Multidimensional Scaling) approach in which the results are expressed in the form of an index and sustainability status. The selection of attributes on each dimension is adjusted to the development of Malang oranges. Determination of attributes for each dimension of sustainability includes 46 attributes in 5 dimensions analyzed, including 10 attributes of the ecological dimension, 9 attributes of the economic dimension, 8 social dimensions, and 10 technological dimensions. Each attribute is modified from several previous studies and adapted to real conditions in the field. The sustainability status of Malang orange cultivation as a whole is included in the fairly sustainable category, namely 69.76%. When viewed from each dimension, there is a dimension that is in the best category with a percentage of 77.23%, namely the economic dimension while the other dimensions are quite sustainable with a percentage below 75%.